Production, optimization, and physicochemical characterization of biodiesel from seed oil of indigenously grown Jatropha curcas - Haq, Abdul; Laiq Ur Rehman, Mian; Rana, Qurrat ul Ain; Khan, Alam; Sajjad, Wasim; Khan, Haji; Khan, Samiullah; Shah, Aamer Ali; Hasan, Fariha; Ahmed, Safia; Islam, Arshad; Badshah, Malik; et al. (Frontiers in Energy Research, 2023)
98% biodiesel at optimized conditions: oil to methanol molar ratio 1:6, KOH 1%, time 90 minutes, and temperature 60 °C. Similarly, Bacillus subtilis Q5 strain yielded 98% biodiesel at optimized condition: oil: methanol ratio of 1:9, agitation 150 RPM, inoculum size 10%, temperature 37 °C and n-hexane 10%. Moreover, factors such as oil-to-methanol molar ratio, amount of catalyst, time, and temperature were optimized and the highest volumetric biodiesel yield obtained was 98% at optimized conditions. The optimized conditions for maximum biodiesel yield were oil to methanol molar ratio 1:6, KOH 1%, time 90 minutes, and temperature 60 °C. The fuel properties of J. curcas seed biodiesel are closely related to standard values specified by American Society for Testing and Materials ( ASTM D6751-20a), indicating its potential as a viable biodiesel fuel source ASTM D6751.